DESAIN MODEL PEMBERDAYAAN DOSEN DI KOTA MEDAN - Agustini, Fauzia; Amanah, Dita; Harahap, Dedy Ansari (Program Studi Pendidikan Manajemen Perkantoran, 2018)
Human resource management in universities especially for lecturers needs to be directed to lecturers empowerment which is an activity aimed to maintain and improve the ability, performance and productivity of lecturer's work in their role as academic staff. One of the factors that can encourage the improvement of work productivity is the empowerment of human resources, as one of the organizational resources.In terms of ensuring the success of the learning process in universities, it is necessary to have a model of human resource empowerment that describes a series of processes performed gradually in order to achieve optimal results so that it will succeed in improving the productivity of lecturer work on an ongoing basis.This model is only tailored to the needs of the college and lecturers who work at the college. This research has designed the lecturer empowerment model which is the development of the human resource empowerment model that has been applied for company employees. This research relates to the needs of lecturers and adapted to the tasks of lecturers at a university, especially in Medan.